AKTIVITAS ANTIBAKTERI DAUN TEBU (Saccharum officinarum) TERHADAP PERTUMBUHAN BAKTERI Salmonella typhi PENYEBAB DEMAM TIFOID - Indah Pratiwi; Cikra Ikhda N H S (Akademi Farmasi Yarsi Pontianak, 2023)
ABSTRACT Typhoid fever is an easily transmitted disease caused by the bacterium Salmonella typhi. Treatment of typhoid fever still uses antibiotics, namely chloramphenicol. Sugarcane leaves contain bioactive compounds Flavonoids and tannins which act as antimicrobials. This study aims to determine the activity of sugarcane leaves in various doses using the maceration extraction method and the pouring method of cultivating bacteria. The research method used is true experiment design research. This research consisted of extract preparation, NA (Nutrient agar) media preparation, chloramphenicol positive control and Aquades negative control preparation. extract dilution with concentration series of 20%, 40%, 60%, 80%, and 100% using distilled water, planting bacteria on media, making MC. Farland, after 24 hours of incubation at 37oC, disc diffusion was planted, and evaluated by measuring the diameter of the clear zone around the bacteria and calculating the inhibition zone. The results of this study showed that sugarcane leaf extract with concentrations of 20%, 40%, 60%, 80%, and 100% did not have an inhibition zone. The conclusion from this study proved that sugarcane leaf extract had antibacterial power against Salmonella typhi with an effective concentration when using this type of solvent. the good one.